KEMAMPUAN PENALARAN DAN KOMUNIKASI MATEMATIS BERDASARKAN KEMAMPUAN AWAL MAHASISWA MELALUI E-LEARNING BERBANTUAN PROGRAM MAPLE - Jusep Saputra; Taufik Rahman (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2022)
Mathematical reasoning and communication skills were added by NCTM and PISA as process standards in mathematics learning that received special attention. The population in this study were all students of Mathematics Education, Pasundan University. The sample in this study was two classes, namely semester 3. The research design used was One-Group-Pretest-Postest. The conclusions of this study include (1) the mathematical reasoning and communication abilities of prospective teacher students after receiving learning with e-learning assisted by the Maple Program are better than before receiving learning; (2) The mathematical reasoning ability of the superior group > moderate group > the low group significantly; (3) The increase in students' mathematical reasoning abilities is in the medium category. The increase in mathematical reasoning ability of the superior group > moderate group > the low group, only not significant; (4) The mathematical communication ability of the superior group > moderate group, it's justnot significant. The superior group > significant assessor group, and the moderate group > significant assessor group; (5) The improvement of students' mathematical communication skills are in a low category. Improved mathematical communication skills of the superior group > moderate group, and the superior group > the low group significantly. Medium group > low group, only not significant.